EFFECT OF ECONOMIC RECESSION ON SOCIAL INEQUALITY - Bipul Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
The death rates of populations in affluent nations tend to increase during economic downturns, which is rather counterintuitive. Economic downturns during the 20th century were linked to decreases in death rates, which runs counter to what one may have anticipated based on historical precedent. Death rates are procyclical, which means that they rise during times of economic growth and fall during times of economic contraction; contrary to popular belief, mortality rates do not fall during times of economic recession. Therefore, while the rates of death in the majority of countries have been falling steadily throughout the course of the previous century, the rate of drop has been slower during times of economic expansion and larger during times of economic contraction. Although the idea has been around for quite some time, it wasn't until the past nine years that there were any serious research that demonstrated this pattern. On the other hand, shared economic progress tends to have a beneficial effect on the health of underdeveloped nations by making it possible to satisfy fundamental requirements such as securing food, clean water, and shelter, in addition to giving access to fundamental medical services. However, when a country hits 5000 to 10,000 gross national product (GNP) per capita (or gross domestic product or gross national income per capita, all of which are equivalent for the purposes of our discussion here), there are little health gains that derive from additional economic expansion. The deteriorating state of health in Sweden is one example of this impact.